PERAN INDONESIA TERHADAP KRISIS KEMANUSIAAN DI MYANMAR MELALUI KEBIJAKAN CONSTRUCTIVE ENGAGEMENT TAHUN 2014-2017 - Amalia, Suci Fitri; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The plight of the Rohingya, an ethnic group in Myanmar who has been suffering an institutionalised persecution and discrimination since the administration of military Junta. The Rohingya is facing a serious threat of genocide, ethnic cleansing and crimes against humanity, while the government of Myanmar has failed in its primary duty to protect them as citizen.The sources of this research are obtained through literature review, other books, website, etc. The sources analysis is qualitative methode. This research uses a level analysis of international system, a perspective of constructivism that describes a solution due to the impact of human’s thought construction and a concept of constructive engagement as a solution of humanity crisis.Due to such failure, the responsibility to protect them falls on the international community included Indonesian to prevent the occurence of mass atrocities under the Constructive Engagemnet. The objective of this mini thesis are to provide an understanding of the plight of the Rohingya and to analyse the Constructive Engagement as a solution of crisis.Key Words: Constructive Engagement, Rohingya, Indonesia’s Policy.